Proposed new interior design of showroom and office for Janggut Printing Enterprise at Lot G13a &113a, Block 2, Laman Seri Business Park, Persiaran Sukan, 40100 Shah Alam, Selangor Darul Ehsan / Mohamad Akmal Abdl Latib - Abdl Latib, Mohamad Akmal (Faculty of Architecture, Planning and Surveying, 2011)
A final year student pursuing a diploma course in Interior Design is requisite to organize a final year project. All the design must be connected to the project that has been decided. Before making the design, major aspect must be considered to get the information. The research, case study, design schematic and the planning have to be done to make sure that client will give the good reaction to our design. Because of that, the organized work must been done perfectly starting from the design development until the end of the project. Proposed new interior design scheme of showroom and office for Janggut Printing is one of it include what occur in client and customer need. It also requested to build a Janggut printing showroom and office so that can fill all customer and client needs. Generally, Janggut printing need to share with their clients all of their products. At the same time they need to give comfort space and good facilities to customers. According to the objectives and the issues, a space planning must be suitable with the design concept and images. So, to realize the design into space is a difficult way because it has the procedures that must be followed. The planning has been produced and the ideas that wanted to be applied into the space must be linked to the concept and images. By that, the good design is produced with the concept, the images, into the design axis and followed by the development of ideas. Guiding customer needs, design that will be molded are applying sustainable design and green design.